Mushroom oils: A review of their production, composition, and potential applications - Tan, Rui Yeong; Ilham, Zul; Wan-Mohtar, Wan Abd Al Qadr Imad; Abdul Halim-Lim, Sarina (Elsevier, 2024)
This review delves into the world of mushroom oils, highlighting their production, composition, and versatile applications. Despite mushrooms' overall low lipid content, their fatty acid composition, rich in essential fatty acids like linoleic acid and oleic acid, proves nutritionally significant. Variations in fatty acid profiles across mushroom species and the prevalence of unsaturated fats contribute to their cardiovascular health benefits. The exploration extends to mushroom essential oils, revealing diverse volatile compounds through extraction methods like hydrodistillation and solvent-assisted flavor evaporation (SAFE). The identification of 1-octen-3-ol as a key contributor to the distinct “mushroom flavor” adds a nuanced perspective. The focus broadens to applications, encompassing culinary and industrial uses with techniques like cold pressing and supercritical fluid extraction (SFE). Mushroom oils, with their unique nutritional and flavor profiles, enhance gastronomic experiences. Non-food applications in cosmetics and biofuels underscore the oils' versatility. The nutritional composition, enriched with essential fatty acids, bioactive compositions, and trace elements, is explored for potential health benefits. Bioactive compounds such as phenolic compounds and terpenes contribute to antioxidant and anti-inflammatory properties, positioning mushroom oils as nutritional powerhouses. In short, this concise review synthesizes the intricate world of mushroom oils, emphasizing their nutritional significance, extraction methodologies, and potential health benefits. The comprehensive overview underscores mushroom oils as a promising area for further exploration and utilization. The characteristics of mushroom biomass oil for the use in various industries are influenced by the mushroom species, chemical composition, biochemical synthesis of mushroom, and downstream processes including extraction, purification and characterization. Therefore, further research and exploration need to be done to achieve a circular bioeconomy with the integration of SDGs, waste reduction, and economic stimulation, to fully utilize the benefits of mushroom, a valuable gift of nature.